Diminished CXCR5 expression in peripheral blood of patients with Sjögren's syndrome may relate to both genotype and salivary gland homing. (24th March 2018) - Aqrawi, L A; Ivanchenko, M; Björk, A; Ramírez Sepúlveda, J I; Imgenberg-Kreuz, J; Kvarnström, M; Haselmayer, P; Jensen, J L; Nordmark, G; Chemin, K; Skarstein, K; Wahren-Herlenius, M
Summary: Genetic investigations of Sjögren's syndrome (SS) have identified a susceptibility locus at p23.3 of chromosome 11, which contains the CXCR5 gene. C-X-C motif chemokine receptor 5 (CXCR5) is a chemokine receptor expressed on B and T cell subsets, and binds the chemotactic ligand C-X-C motif chemokine ligand 13 (CXCL13). In this study we aimed to link the genetic association with functional effects and explore the CXCR5/CXCL13 axis in SS. Expression quantitative trait loci analysis of the 11q23.3 locus was performed using B cell mRNA expression data from genotyped individuals. Lymphocyte surface markers were assessed by flow cytometry, and CXCL13 levels by a proximity extension assay. CXCR5 + and CXCL13 + cells in minor salivary glands were detected using immunohistochemistry. Our results demonstrated that SS-associated genetic polymorphisms affected the expression of CXCR5 ( P  < 0·01). Notably, a decreased percentage of CXCR5 + cells, with lower CXCR5 expression, was observed for most circulating B and T cell subsets in SS patients, reaching statistical significance in CD19 + CD27 + immunoglobulin (Ig)D + marginal zone ( P  < 0·001), CD19 + CD27 + IgD – memory ( P  < 0·05) and CD27-IgD double-negative ( P  < 0·01) B cells and CD4 + CXCR3 – CCR6 + Th17 cells ( P  < 0·05). CXCL13 levels were increased in patient plasma ( P  < 0·001), and immunohistochemical staining revealed expression of CXCL13 and higher numbers of CXCR5 + cells ( P  < 0·0001) within focal infiltrates and interstitially in salivary glands of SS patients. In conclusion, we link a genetic susceptibility allele for SS to a functional phenotype in terms of decreased CXCR5 expression. The decrease of CXCR5 + cells in circulation was also related to homing of B and T cells to the autoimmune target organ. Therapeutic drugs targeting the CXCR5/CXCL13 axis may be useful in SS. Graphical Abstract: